Nutcracker Syndrome combined with Superior Mesenteric Artery Syndrome in a Pediatric Patient: A Case Report - Kyung Wook Min; Oh Kyung Lee; Mi Kyung Kim (Korean Society of Pediatric Nephrology, 2018)
Nutcracker syndrome is a phenomenon that the left renal vein (LRV) is pressed between the superior mesenteric artery (SMA) and the aorta. Clinical characteristics include gross or microscopic hematuria, orthostatic proteinuria, abdominal pain, and back pain. It occurs due to LRV squeezing caused by narrowed aortomesenteric angle. SMA syndrome is a disease that the third part of the duodenum is prone to intestinal obstruction by narrowed angle between the SMA and the abdominal aorta. Clinical symptoms include postprandial abdominal distension, epigastric pain, nausea, and vomiting. SMA syndrome and nutcracker syndrome have common features that result from narrowed aortomesenteric angle. However, it is very rare for both syndromes to occur simultaneously, so the two syndromes are regarded as separate diseases. This is a report on a case of nutcracker syndrome with SMA syndrome in a child who presented gross hematuria, recurrent abdominal pain and vomiting. To our knowledge, nutcracker syndrome simultaneous with SMA syndrome has not been previously reported in pediatric patient, especially with an exhibition of gross hematuria. This case suggests that the simultaneous presence of SMA syndrome with the same pathogenesis needs to be considered when nutcracker syndrome is suspected in pediatric patients with hematuria.